Los mapas de la Nueva Geografía de Colombia de Francisco Javier Vergara y Velasco (1901-1902) - David Alejandro Ramírez Palacios (Confins)
The works of the Colombian geographer, cartographer and historian Francisco Javier Vergara y Velasco (1860-1914) —and his cartographic works in particular—, is beginning to be known and valued by Colombian and international historiography. His maps, wood-engraved, sum up more than two hundreds, most of them distributed between the final edition of his Nueva Geografía de Colombia (1901-1902) and his Atlas completo de geografía colombiana (1906-1910). This paper aims to describe and characterize the set of maps belonging to the Nueva Geografía de Colombia. This is a wide, rich and variegated cartographic collection, based in strong erudition and arduous collection and processing of data, making it a relevant and original work. The set of thematic maps on the book is highlighted.